The effect of collectivism-based organisational culture on employee commitment in public organisations. (October 2022) - Triguero-Sánchez, Rafael; Peña-Vinces, Jesús; Ferreira, João J. Matos
Abstract: In the context of public organisations, this research explores the effect that a collectivism-based organizational culture may have on employee commitment (EC) from a triple perspective - affective, normative, and continuance . A sample of 214 employees of public organisations in Spain was used, and the data were analysed through the Structural Equation Model (SEM). The findings show that the prevalence of collectivism in public organisations favours higher levels of employees' commitment. Such commitment can be seen in the employees' intention to remain in the organisation to provide their services or their emotional attachment. The following research contributes to expanding upon HRM-literature in several ways. First, it assumes a broader view of social exchange theory, highlighting EC's importance when planning HRM in the public sector. Second, it considers the cultural environment (i.e., collectivism-based organisational culture) of public entities as determinants of procommitment policies or policies governing public employees. Highlights: Effect of collectivism-based organizational culture on employee commitment. Employee commitment from a triple perspective - affective, normative, and continuance. Prevalence of collectivism in public organisations favours higher levels of employees' commitment. Cultural environment of public entities as determinants of policies governing public employees.